L’ethique contemporaine a l’epreuve des neurosciences: La problematique philosophique de la conscience - Magliacane, Alessia (Revista Brasileira de Direito Animal, 2019)
Conscience is an emergent phenomenon on the evolutionary scale. Yet is it also a fundamental ethical basis on philosophical views concerning subjectivity and identity, both human and not human. Psychanalysis enlarged the subjectivity sphere by introducing an unconscious level for emotions and symbols. Finally, recent results of neurosciences confirm that we can admit a separation among conscience, subjectivity, identity and intentionality. In this article the author analyses the intersections among scientific results, neurological theories, philosophical contributions, and epistemological-phenomenological views, by adding an animalist position, and aims at a former presentation of some perspectives in ethics and bioethics, arising from this problematic encounter of different interpretations of human conscience.